Spiritually oriented psychotherapy for trauma - Walker, Donald F. (Donald Franklin); Courtois, Christine A.; Aten, Jamie D. (American Psychological Association, 2015)
"This book is intended for psychotherapists working with traumatized clients in a range of settings. We focus on recent developments that have fostered greater sensitivity to spirituality in the ways psychotherapists understand and treat trauma. For many years, clinicians neglected the links between religion, spirituality, and trauma or, worse, viewed religion and spirituality stereotypically as forces that interfered with health and well-being. This book helps to provide an important corrective to that bias. This volume has several themes. First, the chapters integrate research and practice. Throughout, we highlight emerging empirical literature that underscores how trauma can affect people not only psychologically, socially, and physically but spiritually as well. In doing so, chapter authors provide case examples and clinical illustrations that bring the empirical findings into sharper, more human focus. Second, the book is balanced, pointing to both the potentially helpful and harmful ways in which religion and spirituality can affect adjustment to trauma. Finally, we attempt to avoid the kind of spiritual reductionism that has plagued work in the field (i.e., spirituality is merely a source of anxiety reduction, social connectedness, control, meaning). A number of the chapters focus on the impact of trauma on spirituality as an important issue in itself and as a target for change. In doing so, we acknowledge that there are both healthy and unhealthy aspects to spirituality. Our hope is to help clinicians differentiate between healthy and unhealthy forms of spirituality across different populations of traumatized clients. Toward that end, the chapters cut across a broad cross section of presenting problems, with specific focus on relational forms of trauma, such as sexual abuse, partner violence, and other familial forms of trauma. Although the chapter authors have unique theoretical backgrounds, there is some emphasis on psychodynamic treatment for adults as well as cognitive behavior therapy for children throughout the book. In compiling the chapters, we sought case studies reflecting a range of racial and ethnic backgrounds, as well as varying spiritual and religious traditions. Though we were largely successful in this regard, there is some emphasis on Christian religious traditions, broadly speaking, because many of the authors and much of the research in this area are from this tradition. Our hope is that this book will help move spirituality from a peripheral interest at best among mainstream trauma researchers and practitioners to a construct and process of central value"--Introduction. (PsycINFO Database Record (c) 2014 APA, all rights reserved).